Forest ecosystem services: what is it and who benefits from it? / Nurul Akmaniza Mohd Nasir and Nor Hanisah Mohd Hashim - Mohd Nasir, Nurul Akmaniza; Mohd Hashim, Nor Hanisah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
It is always known that forest provides us with a range of benefits such as natural resources supply, high-quality water supply, sites for recreational activities, and a natural habitat for diverse flora and fauna. Today’s growing urbanization results in the need for outdoor recreation and recreational forest offers a place to enjoy the natural beauty of the environment. Currently, the planning and management of recreational forests in Malaysia are focusing on the provision of leisure activities and preserving the forest ecosystem's biodiversity. Due to the nature of growing needs for socio-economic growth and demands for the development of society, the usage of forest ecosystem services eventually brings negative effects. The condition of the environmental setting in a forest is impacted because of the excessive deterioration of natural resources and improper management of biodiversity conservation efforts.